Evaluation of Safety and Efficacy of Combined Low Dose Aspirin and Warfarin Following Mechanical Heart Valve Replacement for Mitral Valve Disease (Bangladesh Heart Journal, 2021)
Introduction: Warfarin is recommended following mechanical valve replacement to prevent thromboembolic complications. A combination of warfarin and aspirin may further reduce thromboembolic events in these patients. This study was designed to evaluate safety and efficacy of combined low dose aspirin and warfarin therapy following mechanical mitral valve replacement.Materials and Methods: Purposively selected 99 patients who underwent mechanical mitral valve replacement were divided into two groups. Patients of Group A (n=50) received combined low dose aspirin (75mg) and warfarin. Patients of Group B (n=49) received conventional dose of warfarin alone. International normalized ratio (INR) was targeted 1.8-2.4 for group A Patients and 2.5-3.5 for group B Patients. Post-operatively INR, thromboembolic events, anti-coagulation related haemorrhage and other morbidity and mortality were registered in both groups.Result: Patients were followed up postoperatively for 9 months. The mean dose of warfarin in group A and group B was 4.36 ± 0.31 mg and 5.57±0.52 mg respectively (p